THE AFTERMATHS OF UNMANAGED TEACHER-TEACHER PROFESSIONAL RELATIONS IN SENIOR HIGH SCHOOLS IN THE TAMALE EDUCATION METROPOLIS, GHANA - Mohammed, I; Abdulai, N.; Suhiyini, B. H. Adam (International Journal of Research -GRANTHAALAYAH, 2023)
The study adopted the qualitative research approach to understand the lived experiences of teachers with regard to the aftermaths of unmanaged teacher-teacher professional relations in senior high schools in the Tamale Education Metropolis. A purposive sampling technique was used to select fifteen (15) secondary school teachers. Face-to-face in-depth individual interviews were conducted. Data were collected through the use of the Pen-and-Paper Personal method. Thematic analytical method was used to analyse collected data. Findings were that the aftermaths of unmanaged teacher-teacher professional relations in schools include teacher stress and burnout, teacher inadequate belongingness and motivation, chaos and conflict, inadequate team spirit and collaboration among teachers, uncooperative teacher behaviours and inadequate knowledge and information sharing among teachers. Recommendations made were that school management in meetings should create rooms where there is open communication and adequate interactions among all teachers and where all teachers are encouraged to develop strong love, care and concern for the well-being and happiness of colleague teachers. The school management should work with the Ghana Education Service to train and equip all teachers on strategies to deal and cope with stress as a result of poor teacher-teacher relations. Team-building exercises should be organized by school management where experts in Team Building are invited to educate and instill in all teachers the need for them to have a high level of team spirit.